Autoethnography as Pedagogy: Writing the "I" in IR. (November 2019) - Barr, Michael
While autoethnography has established itself as a research method, its utility in the classroom remains underexplored. Many writers use autoethnography to describe their roles as educators and students but far fewer detail an actual autoethnographic course. I analyze a highly original MA-level class on autoethnography in international relations. Students report that the course had the "potential to revolutionize" learning and teaching as a means of questioning themselves in relation to the social and political worlds they studied. Autoethnography has transformed the way we approach ourselves and our research; it is now time we let it change how we teach.